2012
DOI: 10.4103/0976-3147.98213
|View full text |Cite
|
Sign up to set email alerts
|

Effect of fluoride exposure on the intelligence of school children in Madhya Pradesh, India

Abstract: Objective:To assess the relationship between exposure to different drinking water fluoride levels and children's intelligence in Madhya Pradesh state, India.Materials and Methods:This cross-sectional study was conducted among 12-year-old school children of Madhya Pradesh state, India. The children were selected from low (< 1.5 parts per million) and high (≥1.5 parts per million) fluoride areas. A questionnaire was used to collect information on the children's personal characteristics, residential history, medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
35
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(38 citation statements)
references
References 17 publications
1
35
2
Order By: Relevance
“…12 However, most of the 27 cross-sectional studies were conducted in areas of rural China that have high levels of naturally occurring fluoride in the water ranging from 2 to 11 ppm, which is approximately 3-16 times higher than optimal fluoride concentrations in Canada. 12 Not included in the aforementioned meta-analysis, eight additional cross-sectional studies performed in India (n = 4), [13][14][15][16] Iran (n = 1), 17 Mexico (n = 1) 18 and China (n = 2) 19,20 found that children classified as having "high" fluoride exposure (defined in various ways) scored lower on some or all components of metrics used to assess intelligence or cognition. In contrast, a prospective cohort study by Broadbent et al found no significant differences in IQ scores between New Zealand children living in fluoridated versus those living in non-fluoridated communities, adjusting for several potential confounders.…”
mentioning
confidence: 99%
“…12 However, most of the 27 cross-sectional studies were conducted in areas of rural China that have high levels of naturally occurring fluoride in the water ranging from 2 to 11 ppm, which is approximately 3-16 times higher than optimal fluoride concentrations in Canada. 12 Not included in the aforementioned meta-analysis, eight additional cross-sectional studies performed in India (n = 4), [13][14][15][16] Iran (n = 1), 17 Mexico (n = 1) 18 and China (n = 2) 19,20 found that children classified as having "high" fluoride exposure (defined in various ways) scored lower on some or all components of metrics used to assess intelligence or cognition. In contrast, a prospective cohort study by Broadbent et al found no significant differences in IQ scores between New Zealand children living in fluoridated versus those living in non-fluoridated communities, adjusting for several potential confounders.…”
mentioning
confidence: 99%
“…17 Saxena et al and Shivaprakash et al in their study have also demonstrated that intellectual capacity of children decreases with increase in the fluorosis grade. 6,19 Data from previous studies support to the hypothesis that interaction between fluoride, lead, and arsenic could worsen the children's intelligence grades, 20 and thus, indicate a need for further investigation. Guan et al demonstrated that the contents of phospholipids and ubiquinone are altered in the brain of rats affected by chronic fluorosis, and therefore changes in membrane lipids could be a cause of this disorder.…”
Section: Discussionmentioning
confidence: 72%
“…Data from previous studies could lend support to the hypothesis that interaction between fluoride, lead and arsenic could worsen the children's intelligence grade and thus indicate a need for further investigation. 6 There is limited evidence on fluoride levels in water level across the country and so its association with dental fluorosis and intelligence of children. In addition, the fluoride levels in water bodies differ from region to region and are not uniform.…”
mentioning
confidence: 99%
“…Liu et al, 2010a;Y.J. Liu et al, 2010b), and the reduced intelligence quotient of children living in areas with endemic fluorosis (Rocha-Amador et al, 2007;Saxena et al, 2012;Tang et al, 2008) are particularly noteworthy. Earlier, we proposed that oxidative stress is an important factor in the multiple systemic damage associated with chronic fluorosis (Gao et al, 2008;Guan et al, 2000) and several studies support this hypothesis (Bharti and Srivastava, 2009;Wang et al, 2000Wang et al, , 2011.…”
Section: Discussionmentioning
confidence: 95%